PERANAN KECERDASAN EMOSI DAN DUKUNGAN SOSIAL TERHADAP KESEJAHTERAAN PSIKOLOGIS PADA SISWA SMP TERBUKA - , TRIANA INDRAWATI; , Prof. Dr. Tina Afiatin, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to prediction psychological well-being in junior high school for low accessibility comunity program students determined by emotional intelligence and social support. Initial assumptions are proposed in this study is emotional intelligence and social support can prediction psychological well-being. The samples in this study were taken 100 students in the junior high school for low accessibility comunity program Cirebon. Samples were taken by using cluster random sampling. Measuring instruments used in the study consisted of 3 scales. First, the scale of which is based on psychological well-being aspects of Ryff (1989) were 30 aitem with a correlation coefficient from 0,312 to 0,590 and an alpha coefficient is 0,887. Second, the scale of emotional intelligence on aspects of the Goleman (2002) which consists is 29 aitem with a correlation coefficient from 0.331 to 0,631 and an alpha coefficient of 0.897. Third, the scale of social support which is based on aspects of Cohen and Syme (1985) which consists of 28 aitem correlation coefficient from 0,350 to 0,624 and an alpha coefficient is 0,895. Methods of data analysis in this study using multiple regression analysis. Regression analysis showed F = 63,883, p = 0,001 (p <0.05) and R2 = 0,568, which means emotional intelligence and social support can prediction psychological well-being of the students junior high school for low accessibility comunity program. Emotional intelligence and social support contributed as much as 56.8% to the psychological well-being.